The Influence of Financial Education on Financial Literacy and Behavior of the Elderly: A Systematic Review - Ani Nuraini; Tiwi Nurhastuti; Hammad; Ati Hermawati; Aisyah Putri Arviani (Asian Journal of Social and Humanities, 2026)
Global population aging poses significant economic risks for older adults. Amid the rapid transition toward technology-based financial systems, older adults face challenges related to digital exclusion, age-related cognitive decline, socioeconomic disparities among low-income households, gender inequalities, and emerging cyber-financial risks. Financial education programs play a vital role as structural interventions to strengthen financial resilience among elderly populations. This research aims to systematically synthesize the effects of financial education programs on financial literacy levels and changes in actual financial behavior among older adults while considering the dynamics of digital financial resilience. This systematic literature review synthesizes evidence regarding the effects of financial education programs on financial literacy and financial behavior transformation among older adults, with consideration of digital financial resilience factors. Following PRISMA guidelines, articles published between 2021 and 2025 were sourced from the Dimensions, Garuda, and Scopus databases, and methodological quality was assessed using the Risk of Bias 2 (RoB 2) tool. The findings revealed age-related declines in financial knowledge, significant gender-based vulnerabilities among older women, and liquidity constraints among low-income household groups. A community-based, offline education model incorporating an age-friendly curriculum and intergenerational support was identified as the most effective intervention approach. Financial education interventions can enhance inclusive financial behaviors among older adults; however, sustaining their long-term impact requires adaptive educational designs and strengthened cybersecurity resilience to support financial protection.